2018
DOI: 10.1016/j.omtm.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Transduction Patterns of Adeno-associated Viral Vectors in a Laser-Induced Choroidal Neovascularization Mouse Model

Abstract: Adeno-associated virus (AAV) vector is a promising platform technology for ocular gene therapy. Recently clinical successes to treat choroidal neovascularization (CNV) in wet type age-related macular degeneration have been reported. However, because pathologic conditions of the retina may alter the tropism of viral vectors, it is necessary to evaluate the transduction efficiency of different serotypes of AAV vectors in the retinas with CNVs. Here, we show the patterns and efficacy of transduction of AAV2, -5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…To determine the functional contribution of Dicer1 deficiency to retinal and choroidal neovascularization in JR5558 mice, we developed a gene therapy capable of restoring Dicer1 activity. We selected adenoassociated vector (AAV) because this modality has demonstrated safety and efficacy in treating blinding diseases in human patients (43,44) and in experimental models of CRNV (45)(46)(47)(48)(49)(50). The human and mouse DICER1 genes are encoded by sequences of 5.7 kb, which is too large to be packaged into a traditional AAV with a size limit of ∼5.2 kb (51, 52).…”
Section: Rpe Degeneration and Aberrant Angiogenesis Due To Dicer1 Lossmentioning
confidence: 99%
“…To determine the functional contribution of Dicer1 deficiency to retinal and choroidal neovascularization in JR5558 mice, we developed a gene therapy capable of restoring Dicer1 activity. We selected adenoassociated vector (AAV) because this modality has demonstrated safety and efficacy in treating blinding diseases in human patients (43,44) and in experimental models of CRNV (45)(46)(47)(48)(49)(50). The human and mouse DICER1 genes are encoded by sequences of 5.7 kb, which is too large to be packaged into a traditional AAV with a size limit of ∼5.2 kb (51, 52).…”
Section: Rpe Degeneration and Aberrant Angiogenesis Due To Dicer1 Lossmentioning
confidence: 99%
“…Immunostaining for various retinal cell markers showed that the targeted retinal cells differed between AAV2- and AAV9-injected diabetic eyes; AAV2 was effectively transduced into RGCs, amacrine cells, bipolar cells, horizontal cells, Müller cells, and microglia, while AAV9 was only transduced into some of the RGCs, Müller cells, and a few horizontal cells. While the different tropisms of AAV serotypes between normal and other pathological retinas were fairly well established in previous studies,14, 22, 23, 24, 25, 26, 27 there has been no report regarding the AAV serotype tropisms in eyes with DR. The results from our study provide further guidance for selecting the most-appropriate AAV serotype when considering targeted ocular gene therapy to treat DR and its related complications.…”
Section: Discussionmentioning
confidence: 93%
“…Tissue processing for immunohistochemistry was performed according to previously published procedures 14, 22. In brief, at 1 month after AAV administration, mice were deeply anesthetized with a 4:1 mixture of zolazepam and tiletamine and xylazine, and intracardial perfusion was performed with 0.1 M PBS containing 150 U/mL heparin, followed by 4% paraformaldehyde (PFA) in 0.1 M PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Specific cell types in the eyes such as retinal pigment epithelium, ganglion, and photoreceptors can be effectively transduced by AAVs, and surgical processes afford access to the various structures in the eye. 127 Non-invasive methods have been established for evaluating therapeutic effects, whereas the contralateral eye can be used as a convenient control. Lastly, numerous genetic animal models have been generated for diseases in the retina, paving the way for gene therapy development.…”
Section: Administrationmentioning
confidence: 99%